Allergic bronchopulmonary aspergillosis without asthma complicating pulmonary tuberculosis - Mansi Gupta (Lung India, 2012)
Allergic bronchopulmonary aspergillosis (ABPA) is typically associated with asthma. Presence of asthma is one of the minimal essential diagnostic criteria for ABPA. Rarely, ABPA has been described in association with other diseases without asthma. It has so far not been known to complicate pulmonary tuberculosis. We report one such case in a young lady where all other diagnostic criteria were fulfilled. The patient responded to corticosteroids and then had acute exacerbations of ABPA twice, each time requiring an increased dosage of corticosteroids as well as itraconazole and responded favorably.